Hermeneutics and Constitutional Mutation: Differences Between Constitutional Mutation (Verfassungswandlung) and Formal Amendment of the Constitutional (VerfassungsÃ¤nderung)- Positioning of the Debate about Art. 52, X CF/98. - Ferreira, Gabriela Vidotti (2012)
The neo-constitutionalist movement is born in a breeding ground of post-World War II to ensure the fundamental rights and limit the Governor’s powers. On these grounds, Brazil issued in 1988, a guarantor and compromised Federal Constitution. In order to have the constitutional "pre-commitments" guaranteed against the social clamor, the Constitution provides “self-restraint” mechanisms, among them, the system of checks and balances. In this constitutionally established system is contained the function of Senate to give efficacy "erga omnes" to the final decisions of the Supreme Court, in the seat of diffuse control of constitutionality. The object of this study is unfolded before this scenario, and starts off with the analysis and differentiation of the institutes of formal amendment of the Constitution and constitutional mutation. To obtain the result, the Heideggerian phenomenological-hermeneutic "method" was used. Thus, this research does not develop a result with absolute truths, but rather, just another view on the topic. With the results, the impossibility of an express constitutional mutation of the item X from article 52 of the Constitution, required in the votes of some ministers in the Constitutional Complaint 4335-5/AC is verified. Keywords: Constitutional Law, Hermeneutics, Constitutional mutation, Formal amendment of the Constitution